Efficacy of chemical and electrical cautery (Comparison) in management of Anterior Epistaxis - Tahira Ikram; Muhammad Umar Asim; Sundas Masood; Aeiman Fatima; Haitham Akash; Zaimal Shahan; Samina Yaqoob (Journal of Rawalpindi Medical College, 2022)
Objective: To compare the efficacy of chemical versus electrical cautery in the management of patients presenting with anterior epistaxis in terms of frequency of bleeding. Materials and Methods: Study Design = Randomized Control Trial (RCT) Study Setting = ENT Department Benazir Bhutto Hospital, Rawalpindi Duration = 6 months Sampling Technique = Consecutive (Non Probability) A Randomized Control Trial (RCT) of six months was done after the approval of the Ethical Committee. A total of 90 cases of anterior epistaxis were randomly divided into two groups: A (electrical cautery) and B (chemical cautery) using a random number trial with 45 in each group respectively. Informed consent was taken from all patients. Patients were explained about the procedure and its risk-benefit ratio. A detailed history was taken about epistaxis from patients presenting in an emergency. The site of bleeding was assessed. Pulse and blood pressure of patients were monitored. Patients were treated on an emergency basis. The nasal cavity was inspected with the help of a nasal speculum and suction of any blood clots was done. Bleeding points were identified and sprayed with lidocaine. The bleeding area was cauterized with a silver nitrate stick or electrical cautery for a few seconds. Antibiotic ointment was applied at the site of cautery to both groups. The patient was discharged on cessation of bleeding. A Performa was given to patients to fill 48 hours, 1 week, and 2 weeks after the procedure containing questions regarding relief of symptoms. Recurrent bleed was diagnosed on a history of separate bleed from nose post-procedure that was sudden in onset, with an identifiable bleeding point on inspection by speculum, total duration of all episodes in previous 24 hours less than 30 minutes. Results: A total of 90 cases (45 in each group) were taken. The mean age was calculated and found 34.42±8.70 in Group-A and 34.29+8.94 years for group B., The male patients were 32 (71.11%) in Group-A and 30 (66.67%) in Group-B while females were 13 (28.89%) in Group-A and 15 (33.33%) in Group-B, efficacy between chemical and electrical cautery in patients with reference to frequency of bleeding was 42 (93.33%) in Group-A and 35 (77.78%) in Group-B, the p value was calculated as 0.03 which shows a significant difference. Conclusion: This study concluded that the efficacy of electrical cautery is significantly higher than chemical cautery in the management of epistaxis. However, some other trials on larger sample size are required to validate the findings of this study.